POTENTIAL OF ANTIOXIDANT PROTECTION IN PATIENTS WITH EPISTAXIS - N. V. BOIKO; T. S. KOLMAKOVA; O. B. SMIRNOVA (Кубанский научный медицинский вестник, 2017)
The status of patients with nose bleedings (NB) depends not only on the volume of blood loss, but also on the degree of compensation for hypoxia accompanying hemorrhage.Aim. The main aim of our research was to study the antioxidant properties of blood serum and the intensity of LPO processes in erythrocyte membranes of patients with epistaxis of varying severity.Materials and methods. 82 patients with nose bleeding of varying severity were examined. The antioxidant activity of the blood serum of patients was studied by the chemiluminescence method induced by divalent iron ions. The processes of lipid peroxidation were studied by evaluating the activity of antioxidant defense enzymes – superoxide dismutase (SOD) and total peroxidase activity in blood erythrocytes, as well as the content of the final product of LPO-malonic dialdehyde (MDA) in erythrocytes.Results. It has been established that the potential of antioxidantprotection of serum and formed elements of blood is one of the most important links in the pathogenesis of NB.Conclusion. High capacity of antioxidant protection can significantly reduce the risk of irreversible changes in erythrocytes and the development of clinical signs of deep tissue hypoxia in patients with epistaxis.